Epithelial Myoepithelial Carcinoma- A Rare Case Report (Bangladesh Journal of Medical Science, 2012)
Background: Salivary gland tumors occupy an imperative part while considering the entire spectrum of tumor pathology occurring in the maxillo-facial and cervical areas. They often pose diagnostic uncertainty due to intrinsic architectural and cytologic complexity, overlapping architecture. Epithelial-myoepithelial carcinoma is a rare tumor, constituting 1% of all salivary gland tumors. Methods and Results: We present a case of Epithelial-myoepithelial carcinoma in a 55-year-old male who presented with paresthesia of lower lip and swelling of the right side of face . Imaging revealed complete destruction of right ramus with an enhancing soft tissue mass. Patient underwent a surgical excision of the mass, which revealed an Epithelial-myoepithelial carcinoma. Conclusion: Although Epithelial-myoepithelial carcinoma is extremely rare in occurrence, have immense destructive capabilities. Hence a description of clinical presentation, radiographic extension and histopathologic presentation would be of great additive value to the sparse information of this rare tumor DOI: http://dx.doi.org/10.3329/bjms.v11i2.11480 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 129-133